Umweltbewußtsein und umweltbezogene Forschung in Alaska (Das Artic Environmental Information and Data Center in Anchorage) - Schweinfurth, Ulrich (ERDKUNDE, 1979)
Experiences in the temperate latitudes of the southern Pacific requiring comparison in the temperate latitudes of the northern Pacific provided the motivation for going to see Alaska. In the course of studying the literature connected with it, further recent publications were found, which, though not considered here because of their specialist character, will be discussed in connection with the comparisons that are planned. The chief aim of the present report is to sketch the main features of development in Alaska as it has presented itself in the course of the last decade. This is a development which forces the country into environmentally conscious action on two fronts simultaneously: in the country's interior as well as at sea. The establishment of the A.E.I.D.C. in Anchorage appears to guarantee the success of the young country in meeting the challenge on both fronts